Low level of tracheal cellular fibronectin in extremely premature infants with funisitis: Relationship with respiratory distress 1 month after birth. Issue 9 (24th October 2013) - Arai, Hirokazu; Ito, Tomoo; Adachi, Hiroyuki; Goto, Ryoji; Takahashi, Tsutomu
Summary Background Funisitis reflects the fetal systemic inflammatory response in premature infants. Macrophages and neutrophils have been identified as key elements in the inflammatory process of the lungs, and secrete proteases that cause the destruction of the extracellular matrix (ECM). Fibronectin (FN) is the major constituent of the pulmonary ECM and exists in multiple isoforms arising from alternative RNA splicing. Extra domain A (EDA) is the major alternatively spliced segment, and the expression of EDA containing FN (EDA + FN) in the lungs is associated with distal pulmonary cell proliferation during alveolar formation. Objective To study the relationship between the presence of funisitis and EDA + FN levels in the tracheal aspirate fluid (TAF) of infants of less than 28 weeks' gestation. Methods The subjects included in this study were 26 extremely premature infants of <28 weeks' gestation at <24 hr of age, from whom the TAF was collected. These preterm infants were divided into two groups according to placental histology. The funisitis (+) group (n = 9) was compared with the funisitis (−) group (n = 17). The TAF supernatants were analyzed for IL‐1β, IL‐6, IL‐8, neutrophil elastase, and EDA + FN using enzyme‐linked immunosorbent assay (ELISA). Results There were no significant differences in gestational age or birthweight between these groups. The funisitis (+) group had a significantly higher ventilator setting (inspired O2 × mean airway pressure) at Day 28 than the funisitis (−) group. In the TAF, the concentrations of IL‐1β were significantly higher in the funisitis (+) group than in the funisitis (−) group, as were the concentrations of neutrophil elastase. The concentrations of EDA + FN were significantly lower in the funisitis (+) group than in the funisitis (−) group. Conclusions Decreased EDA + FN in TAF might be one of the risk factors leading to respiratory distress in extremely premature infants with funisitis. Pediatr Pulmonol. 2014; 49:905–910. © 2013 Wiley Periodicals, Inc.